The effects of high amounts of Al and Zn on the structural properties of hydroxyapatite prepared by sol-gel method - Tatar, Cengiz; Bagci, Dilek; Kaygili, Omer (Korean Assoc Crystal Growth, Inc, 2016)
In the present study, the effects of high amounts of Al and Zn additives on the crystal structure, phase composition and microstructure of hydroxyapatite (HAp) samples synthesized by sol-gel route were investigated by X-ray diffraction (XRD), Fourier transformation infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) techniques. The values of the crystallinity percent, crystallite size, lattice parameter of a and volume of the unit cell decrease gradually with increasing amount of the co-additives. The formation of the new phases is observed and these phases become dominant with increasing amount of Al and Zn. The morphology of HAp, shape and size of the particles are also affected by the amount of Al and Zn. As expected, a gradual decrease in the Ca/P molar ratio is observed.
Keywords: Hydroxyapatite; Crystal Structure; Crystallinity Percent; Scanning Electron Microscopy (SEM); X-ray diffraction (XRD)